Improvement of Student's Critical Thinking Ability sin Physics Materials Through The Application of Problem-Based Learning - Samadun Samadun; Dwikoranto Dwikoranto (IJORER : International Journal of Recent Educational Research, 2022)
Students' skills in critical thinking are needed in learning for problem-solving. The purpose of this study was to analyze the concept of problem-based learning models, the implementation of problem-based learning models in improving students' critical thinking skills, the effectiveness of problem-based learning models in improving students' critical thinking skills, as well as the effect of problem-based learning models on improving high school students critical thinking skills. on physics. The method in this research is a descriptive research method through literature study. In this study, the results of a review of several articles related to the problem-based learning model were obtained. Based on the research that has been done, it can be concluded that the problem-based learning model is a problem-based learning model directly so that students are active in learning in class. The implementation problem-based learning model can train students to overcome various problems directly so that they can improve students critical thinking skills. The application of problem-based learning model is very effective when applied in the student learning process in the classroom because it can improve students' critical thinking skills. The application of the problem-based learning model affects improving high school critical thinking skills on physics material.